Effect of crystal orientation on the hardness and strength of piezoelectric LiNbO3 substrates for microelectronic applications. (January 2022) - Gruber, M.; Leitner, A.; Kiener, D.; Supancic, P.; Bermejo, R.
Graphical abstract: Highlights: Hardness anisotropy associated with crystal orientation governs surface damage morphology in LiNbO3 . A 20% difference in hardness can double the characteristic strength of LiNbO3 . Tailored high Young's modulus surface planes of LiNbO3 can significantly increase its characteristic strength. Abstract: Piezoelectric single crystalline materials are paramount for high-speed data transfer in 5G technologies. The functionality of the end-devices demands temperature independent frequency filtering and high surface acoustic wave velocities, which are associated with the orientation dependent thermo-physical properties of the piezoelectric substrate material. Single crystalline Lithium Niobate (LiNbO3 ), cut in particular directions, has proven to have outstanding functional properties, yet its brittle character along with the highly anisotropic mechanical properties may limit its use in demanding applications. In this study, the effect of crystal orientation on hardness and on mechanical strength is demonstrated by comparing nanoindentation results and finite element analysis supported biaxial strength experiments for two LiNbO3 samples with different orientation. It is demonstrated that the crystal anisotropy leads to differences in hardness up to ∼ 20% between both orientations, with the characteristic strength being double in the harder direction. The observed correlation is rationalized based on the effect of surface finish and distinct sub-surface damage in the corresponding crystal orientations. Additional strength measurements on nano-scratched samples revealed a significantly higher remaining strength for the harder orientation due to less (sub-) surface damage. These findings can be exploited in future design of single crystalline substrate materials with higher reliability.